Human Resources Development Through Scholarship: A Case Study of Ministry of Public Works and Housing of Indonesia - Abdullatif Setiabudi; Muchlis R. Luddin; Yuli Rahmawati (AIBPM Publisher, 2019)
The objective of this research was to evaluate human resources development through scholarship in the Ministry of Public Works and Housing of Indonesia (MPWHI). The study investigated the planning, implementation, and output of the MPWHI scholarship program by method of document analysis, and personal interviews with employees directly involved in the scholarship program at MPWHI. The program evaluation model known as ‘Context, Input, Process, and Product’ (CIPP) was employed to analyze and evaluate the scholarship program. The 50 participants of the study included policy makers, scholarship students, and other stakeholders. Results indicated that while the purpose of the program has been outlined in formal documentation, it is not currently well implemented. Furthermore, the national education regulation (UU No. 20/2003), states that the curriculum of official education should be designed as a professional skills program, while the study concluded that in practice, it focuses on knowledge, rather than skills. Also, it appeared challenging to assess graduates’ competencies and professionalism in the workforce. Improvements in planning, implementing, monitoring and evaluation of scholarship programs would be beneficial. Despite these shortcomings, the results showed that the scholarship program at MPWHI has contributed significantly to enhancing the quality and competencies of human resources. This research is intended to contribute to the improvement of scholarship programs in government organizations.